2021
DOI: 10.1200/jco.2021.39.15_suppl.3066
|View full text |Cite
|
Sign up to set email alerts
|

Validation of FAPi PET biodistribution by immunohistochemistry in patients with solid cancers: A prospective exploratory study.

Abstract: 3066 Background: Fibroblast activation protein (FAP)-expressing cancer-associated fibroblasts (CAF), a major component of tumor stroma, confer treatment resistance, promote local progression, metastasis and immunosuppression. Because FAP is selectively expressed in the tumor stroma of many cancers, radiolabeled small molecule ligands targeting FAP are being explored for their use as pan-cancer theranostic agents. The objective was to establish the spectrum of FAP expression across various cancers by immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…68 Ga-FAP inhibitor-46 is a radiolabeled probe for the in vivo detection of FAP [7,8,34], and its positron emission tomography can be used to detect DVT but not pulmonary emboli in patients with venous thromboembolism [35]. Besides, our previous studies showed that DVT and pulmonary thromboembolism are composed of heterogeneous components of fresh and organizing thrombi [2,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Ga-FAP inhibitor-46 is a radiolabeled probe for the in vivo detection of FAP [7,8,34], and its positron emission tomography can be used to detect DVT but not pulmonary emboli in patients with venous thromboembolism [35]. Besides, our previous studies showed that DVT and pulmonary thromboembolism are composed of heterogeneous components of fresh and organizing thrombi [2,4].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that FAP expression in CAFs contributes to cancer cell invasion, metastasis, and poor outcomes in various primary organs [6]. In the future, it is also expected that targeted FAP imaging will allow the detection of cancer sites [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The implications for FAPI-PET/CT imaging are expected to be limited since Langerhans insulae are de nitely smaller (mean islet diameter of 108.92 µm (± 6.27 µm) [10] than the resolution limit of a PET scanner (2.36 mm FWHM) [11]. According to biodistribution studies, Mona et al found average [ 68 Ga]Ga-FAPi-46 SUVmean at the pancreas to be < 2.5 [12]. Additionally, in the head-to-head comparison, Giesel et al found that mean SUVmax in the pancreas was signi cantly lower for [ 68 Ga]Ga-FAPI than [ 18 F]FDG (1.82 vs. 1.99; p = 0.027) [13].…”
Section: Discussionmentioning
confidence: 99%